Outcomes of bebtelovimab and sotrovimab treatment of solid organ transplant recipients with mild‐to‐moderate coronavirus disease 2019 during the Omicron epoch. Issue 4 (25th July 2022) - Yetmar, Zachary A.; Beam, Elena; O'Horo, John C.; Seville, Maria Teresa; Brumble, Lisa; Ganesh, Ravindra; Razonable, Raymund R.
Abstract: Background: Solid organ transplant recipients (SOTRs) are at high‐risk for severe infection from severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Anti‐spike monoclonal antibodies are currently utilized under emergency use authorization to prevent hospitalization in high‐risk individuals with coronavirus disease 2019 (COVID‐19), including SOTRs. However, clinical data for bebtelovimab, the sole currently available anti‐spike monoclonal antibody for COVID‐19, is limited. Methods: We conducted a retrospective cohort study of adult SOTRs diagnosed with mild‐to‐moderate COVID‐19 from January 2022 through May 2022 who received either bebtelovimab or sotrovimab. The primary outcome was COVID‐19‐related hospitalization within 30 days of COVID‐19 diagnosis. Data were analyzed with Fisher's exact test. Results: Among 361 SOTRs, 92 (25.5%) received bebtelovimab and 269 (74.5%) received sotrovimab. The most common organ transplant was a kidney (42.4%). SOTRs who received bebtelovimab had a higher proportion who had received a booster SARS‐CoV‐2 vaccine dose and had received their last vaccination dose more recently. Eleven (3.0%) SOTRs were hospitalized, and rates of hospitalization were similar between monoclonal antibody groups (3.3% versus 3.0%; p > .99). Three patients required admission to an intensive care unit, all of who received sotrovimab. Four (1.1%) patients died within 30 days of COVID‐19 diagnosis, two from each group. Conclusions: SOTRs with mild‐to‐moderate COVID‐19 who received bebtelovimab had similar rates of COVID‐19‐related hospitalization as those who received sotrovimab. While differences in vaccination rates and viral subvariants could act as confounders, bebtelovimab appears to be of similar effectiveness as sotrovimab. Abstract :